Antioxidant activity of queen bee larvae processed by enzymatic hydrolysis. Issue 2 (7th September 2017) - Dong, Deyuan; Dong, Mengyi; Liu, Kemei; Lu, Yu; Yu, Bo
Abstract: Queen bee larvae (QBL), by‐products of royal jelly processing, was enzymatically hydrolyzed to produce bioactive peptides. Five enzymes were firstly used to obtain hydrolysates which were evaluated for their antioxidative performances. QBL hydrolyzed by pepsin, showing the highest antioxidant resistance, were prepared and isolated by ultrafiltration using different molecular weight cutoffs of <1, 1–5, 5–10, and >10 kDa. Then, hydrolysate III (MW 1–5 kDa) with the highest activity was purified through continuous chromatography. Antioxidant capacities of active peak 3 (P3) to DPPH, hydroxyl, superoxide, ABTS, oxygen radical absorbance capacity radicals assay were 74.31%, 82.44%, 74.53%, 78.81%, and 1, 074 μM TE/g, respectively. Finally, the most potent antioxidant hydrolysate was determined through a high‐speed amino acid analyzer. The results of the QBLH for in vitro antioxidant assays have indicated that P3 is a good antioxidative peptide due to its high percentage of hydrophobic amino acids and has vast prospects for future development and application. Practical applications: QBL has been used as a traditional medicine for several millennia in China due to its rich nutrition and potent effect in improving human immunity, however, the utilization of QBL resources industry is rather low. This article evaluated the antioxidant activities of queen bee larvae using DPPH, hydroxyl, superoxide, ABTS, ORAC radicals assay, respectively. This article indicates that high antioxidant amino acid residues can be obtained from QBL through simple processing methods (enzymatic hydrolyzing and membrane isolating). Our study could arouse a great interest among researchers to develop a new series of QBL products with high efficient antioxidant properties.